Hydraulics engineering problems and solutions - Amat Sairin Demun (Penerbit UTM Press, 2017)
The book presents eight selected chapter of core topics in hydraulics engineering in civil engineering programmes in most universities worldwide. Each chapter consists list of learning outcomes and short discussion of theoretical concepts of selected topics.